A model of tutor agent in collaborative e-learning environment - Muhammad Sani, Salisu; Mohd Aris, Teh Noranis (Institute of Research Engineers and Doctors, 2014)
A collaborative e-learning environment is made up of participants that are remotely placed, who for their diverse social or geographical reasons could not be able to attain their educational goals in the same physical environment. In such collaborating environments, students need to interact and communicate with each other, share their common experiences and solve common problems. This may sometimes results to many collaboration conflicts that may require the intervention by a teacher. Managing such web integrated environments by a human teacher will no doubt be tedious, less efficient and at the same time consuming. The aim of this paper is to introduce a multi-agent approach to model the tutor component by substituting the human teacher with an intelligent tutor agent in order to improve the supervision and mediation against collaboration conflicts tasks of the teacher in such environment.